Determinación del porcentaje de preñez mediante el uso de la hormona GNRH al momento de la inseminación artificial en la ganadería la FACIAG - Elizondo Arreaga, Yoina Faustina (2023)
This research work was carried out in the “Jorge Yánez Castro” livestock area of the Faculty of Agricultural Sciences of the Technical University of Babahoyo. We select the animals that are not pregnant through a gynecological check-up. The animal must have a body condition of 2.5 to 3.5, properly dewormed, vitaminized and keep the appropriate records. On day 0, field work begins and is used. a protocol with an intravaginal device (IVD) of 0.5 grams and also applies 2ml of the hormone estradiol benzoate, trade name (Gonadiol). On day 8 of having applied the devices, we proceed with their removal, and we will apply 3 hormones, which are: Estradiol cypionate 1ml (Cipiocyn) 2 ml of prostaglandin (cloprostenol) 2 ml of equine chorionic hormone (Norvemon). The syringes that were used are 3 ml. On day 10, at 52 or 56 hours, artificial insemination is performed. At the time of A.I., 2 ml of gonadotropin-releasing hormone GNRH (Gonasyn) was applied. For the development of this research, the Completely Randomized experimental design was used, with two treatments (without application of hormone (Control) and gonadotropin-releasing hormone) and ten repetitions. Comparisons of treatments were made with the Tukey test. The conclusion was obtained that the application of gonadotropin-releasing hormone increases the pregnancy percentage with 60% while the control group (without GNRH) with 40% at the time of artificial insemination in female cattle belonging to the farm of the Faculty of agricultural sciences.